The role of ethyl glucuronide in supporting medico-legal investigations: Analysis of this biomarker in different postmortem specimens from 21 selected autopsy cases. (January 2018) - Santunione, Anna Laura; Verri, Patrizia; Marchesi, Filippo; Rustichelli, Cecilia; Palazzoli, Federica; Vandelli, Daniele; Licata, Manuela; Silingardi, Enrico
Abstract: Ethanol determination in postmortem blood is one of the most frequently requested analyses in legal medicine and forensic toxicology. Ethyl glucuronide is a non-oxidative ethanol metabolite. It is also a useful marker of ante-mortem alcohol ingestion when ethanol itself has been completely eliminated from the body and could be considered in autopsy cases to obtain more reliable indications. The aim of the present study was to investigate the ethyl glucuronide distribution in postmortem specimens from autopsy cases found to be positive for ethanol. We presented 21 autopsy cases in which central blood, peripheral blood and liver samples were available. Specimens were analyzed for ethyl glucuronide by liquid chromatography tandem mass spectrometry; we also recorded postmortem interval, case history, cause of death, use of drugs, metabolic disorders if present, putrefaction if present, history of ethanol abuse and information about ethanol intake before death. Our aim was to evaluate and to compare the ethyl glucuronide levels in different matrices taken from the same subject in order to provide a better understanding of the interpretation of postmortem ethyl glucuronide concentrations. Highlights: An analytical method for the quantitative analysis of ethyl glucuronide was validated. The validated method was applied in authentic postmortem samples. The determination of ethyl glucuronide could help to better interpret autopsy cases found to be positive for ethanol.